Patient experience and satisfaction with Onabotulinumtoxin A for refractory overactive bladder. (16th April 2015) - Malde, Sachin; Dowson, Christopher; Fraser, Olivia; Watkins, Jane; Khan, Muhammed S.; Dasgupta, Prokar; Sahai, Arun
<x xml:space="preserve">Abstract</x> Objective To evaluate the patient experience of our dedicated botulinum toxin A (BTX‐A) service using a validated patient‐reported experience measure (PREM) and assess patient‐reported satisfaction with treatment. Materials and Methods The first 100 patients who underwent BTX‐A treatment for refractory idiopathic detrusor overactivity (IDO) in our institution were contacted for telephone interview. They had all been assessed, injected and followed up in a dedicated BTX‐A clinic. Patients were asked to complete a validated PREM – the Client Satisfaction Questionnaire (CSQ‐8) – as well as a questionnaire developed in our department to assess satisfaction with the results of the treatment. Most patients received 200 U OnabotulinumtoxinA (Botox®) via an outpatient local anaesthetic flexible cystoscopy technique. Results Complete data was available for 72 patients. In all, 49 patients were continuing to receive BTX‐A treatment while 23 had opted for no further injections. The overall mean (sd) CSQ‐8 satisfaction score was 38.3 (3.3), indicating a high level of patient satisfaction with the service offered in our institution. There was a significant difference in total satisfaction scores between those still receiving BTX‐A (mean score 29.8) and those who have discontinued treatment (mean score 25.1) (P < 0.01). Overall patient satisfaction with the result of the treatment was high with an overall mean (sd) score of 8.6 (2.0) on a visual analogue scale. Of those who had discontinued BTX‐A, most were either using conservative measures only (44%) or had recommenced anticholinergic medications. Conclusion Overall patient satisfaction with the dedicated BTX‐A service offered in our institution is high and can result in a positive patient experience. The use of PREMs are advocated in order to fully capture the patient's views of the quality of services and treatments they receive.